Level of Physical Fitness and Self-Confidence in Futsal Extracurricular Training at SMP Negeri 11 Pontianak - Feby Arpia; Simanjuntak, Victor Gaperius; Bafadal, Muhammad Fachrurrozi; Hidasari, Fitriana Puspa; Triansyah, Andika (Educational Sciences Journal, 2024)
Physical fitness and self-confidence are very important aspects for success in the game. However, measurements are rarely carried out. This research aims to determine the level of physical fitness and self-confidence of futsal extracurricular students. This research is a descriptive quantitative type of research using a survey method, in this research there are tests and measurements given. The research instrument used TKJI 12-15 years. The subjects in this research were 20 futsal extracurricular participants at SMP Negeri 11 Pontianak. The research results showed that the level of physical fitness among futsal extracurricular students was 16 students in the moderate category with a percentage of 80% and there were 4 students in the poor category with a percentage of 20%. Furthermore, the level of self-confidence among futsal extracurricular students has very good self-confidence, this result is proven by the fact that there are 12 students in the very good category with a percentage of 60% and there are 8 students who have good self-confidence with a percentage of 40%. The results of this study show that it can be concluded that the students' physical fitness is in the medium category. Based on the results of self-confidence in futsal extracurricular students, the average results are in the good category.